2014
DOI: 10.3390/v6114683
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus HBx Protein Interactions with the Ubiquitin Proteasome System

Abstract: The hepatitis B virus (HBV) causes acute and chronic hepatitis, and the latter is a major risk factor for the development of hepatocellular carcinoma (HCC). HBV encodes a 17-kDa regulatory protein, HBx, which is required for virus replication. Although the precise contribution(s) of HBx to virus replication is unknown, many viruses target cellular pathways to create an environment favorable for virus replication. The ubiquitin proteasome system (UPS) is a major conserved cellular pathway that controls several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 116 publications
1
50
1
Order By: Relevance
“…An intriguing speculation coming from previous reports that the HBx-DDB1 interaction is critical for viral genome replication (15,16) was that HBx-targeted host factors that restrict viral DNA replication are regulated by the Cul4-DDB1 ubiquitin E3 ligase (12). Contrary to the expectation of that hypothesis, our findings consistently indicated that the DDB1-HBx interaction is largely dispensable for HBx-stimulated viral genome replication.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…An intriguing speculation coming from previous reports that the HBx-DDB1 interaction is critical for viral genome replication (15,16) was that HBx-targeted host factors that restrict viral DNA replication are regulated by the Cul4-DDB1 ubiquitin E3 ligase (12). Contrary to the expectation of that hypothesis, our findings consistently indicated that the DDB1-HBx interaction is largely dispensable for HBx-stimulated viral genome replication.…”
Section: Discussioncontrasting
confidence: 57%
“…The ␣-helical motif, referred to as the H box (i.e., residues 88 to 100), of the HBx polypeptide was revealed to be an interacting motif that binds directly to one of three ␤-propeller domains of DDB1 (i.e., the BPC domain) (11). Importantly, via its interaction with DDB1, HBx was shown to constitute the Cul4A-DDB1 ubiquitin E3 ligase, implicating a role of HBx in ubiquitin-mediated protein degradation (11,12). An intriguing possibility is that many, if not all, of these attributes of HBx could potentially be related to the DDB1-HBx interaction.…”
mentioning
confidence: 99%
“…Ubiquitin proteasome system (UPS), responsible for the degradation of a majority of intracellular proteins, is partially involved in this process [27]. HBx can interact with components of the UPS, including the CUL4 adaptor DDB1, the cullin regulatory complex CSN, and the 26S proteasome, and then alter the levels of target proteins [28]. Utilization of ubiquitin proteasome machinery by HBx has become one of the strategies for its promotion on HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…DNA tumor viruses, especially EBV, are well known to manipulate the host ubiquitin (Ub) machinery to facilitate their latent persistence and oncogenesis (16)(17)(18)(19)(20). We have provided solid evidence showing that IRF7 is activated by LMP1 through a TRAF6/RIP-dependent, K63-linked ubiquitination pathway (11,12).…”
mentioning
confidence: 84%